1994
DOI: 10.1111/j.1469-8137.1994.tb04244.x
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of CO2and other gases inside leaves

Abstract: SUMMARY Diffusion of CO2 in the intercellular airspaces of the leaf mesophyll is one of the many processes that can limit photosynthetic carbon assimilation there. This limitation has been largely neglected in recent years, but both theoretical and empirical evidence is presented showing that it can be substantial, reducing CO2 assimilation rates by 25% or more in some leaves. Intercellular diffusion is fundamentally a three‐dimensional process, because CO2 enters the leaf through discrete stomata, and not thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
322
0
4

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 353 publications
(336 citation statements)
references
References 73 publications
10
322
0
4
Order By: Relevance
“…Morphological features, such as leaf display and shape, influence light interception and boundary layer thickness, and thus affect light absorption, energy balance and gaseous diffusion. Despite the potential importance of leaf anatomy to the internal distribution of light (Vogelmann 1993) and gases (Parkhurst 1994), little is known about the consequences of variation in internal structure.…”
Section: Introductionmentioning
confidence: 99%
“…Morphological features, such as leaf display and shape, influence light interception and boundary layer thickness, and thus affect light absorption, energy balance and gaseous diffusion. Despite the potential importance of leaf anatomy to the internal distribution of light (Vogelmann 1993) and gases (Parkhurst 1994), little is known about the consequences of variation in internal structure.…”
Section: Introductionmentioning
confidence: 99%
“…In the photosynthetic cells of Ballota, the chloroplasts are arranged just beneath those parts of cell walls exposed to the internal leaf atmosphere and the IES might be the real photosynthetic surface, as suggested by Jarvis & Slatyer (1970). Raven (1993) has pointed out the problems of increasing the rate of photosynthesis per unit area of cell exposed to the gas phase, because of the volume of the chloroplasts and the low diffusion coefficient of CO^ in aqueous solutions, whereas Parkhurst (1986;1994) argues that limited intercellular diffusion might partly explain the existence of distinct palisade and spongy mesophyli tissues. It is likely that the trivial ICS of young tissues reduces the diffusion path of CO2 in the gaseous-phase, whereas it facilitates the transport of water that largely bypasses most mesophyll cells, where it evaporates from their wet cell walls into the intercellular spaces in its movement from the xylem to the stomata (Matsuda & Riazi, 1981;Taiz & Zeiger, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…1990). Mesophyll structure and water status are both related to leaf expansion (Dale, 1988;Parkhurst, 1994). The surface area of mesophyll cells is 10 (or more) times that of the crosssectional area of the leaf available for intercellular gaseous diffusion (Jarvis, 1971) and about 7-30 times its external area (Meidner & Sheriff, 1976;Raven, 1984;Bolbar-Nordenkampf & Draxler.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atkin et al (1998) found evidence for the latter, as canopy N productivity (quotient of net biomass gain and canopy N content) was negatively related to the canopy average for M area across several species of Acacia. The mechanistic link between PNUE (or N productivity) and M area has not been fully resolved, but the available evidence points to limitations on photosynthesis imposed by severe intra-leaf light gradients (Osborne and Raven, 1986;Terashima and Hikosaka, 1995;Reich et al, 1997Reich et al, , 1998) and/or resistance to CO 2 diffusion (Lloyd et al, 1992;Parkhurst, 1994;Poorter and Evans, 1998;Garnier et al, 1999) within high-M area leaves. The observed curvilinearity in the relation between ε and the index (Fig.…”
Section: Mechanistic Links Between ε and The Indexmentioning
confidence: 99%